GAMBARAN PENGELOLAAN PENYIMPANAN OBAT DI GUDANG FARMASI RUMAH SAKIT UMUM DAERAH BANGKINANG TAHUN 2017 - Sri Rezki Ani (Jurnal Penelitian Farmasi Indonesia)
Storage is an activity of storing and maintaining by placing a pharmaceutical supply received at a place deemed safe from theft as well as physical disturbance that may damage the quality of the drug. This study aims to see the description of drug storage management in pharmacy warehouse of Bangkinang Public Hospital in accordance with Management Guidance of Pharmaceutical Supplies in Hospital from Directorate General of Pharmaceutical Development and Health Equipment of Ministry of Health RI In cooperation with Japan International Cooperation Agency in 2010. This research is an observational research which is descriptive and data collection is done cross sectional by filling the checklist sheet. The results obtained indicate that the requirements of the warehouse and recording of the stock have been in accordance with the requirements while the storage / preparation of the drug has not been eligible. The requirements of the medicine warehouse with the percentage of 90.91% (very good), the requirement of storage / preparation of drugs with the percentage of 55.56% (good enough) and the requirements of drug stock listing system with the percentage of 87.5% (very good).